A Flexible Dual-Mode Photodetector for Human–Machine Collaborative IR Imaging - Fang, Huajing; Xie, Xinxing; Jing, Kai; Liu, Shaojie; Chen, Ainong; Wu, Daixuan; Zhang, Liyan; Tian, He (Nano-Micro Letters, 2025)
Photothermoelectric (PTE) photodetectors with self-powered and uncooled advantages have attracted much interest due to the wide application prospects in the military and civilian fields. However, traditional PTE photodetectors lack of mechanical flexibility and cannot operate independently without the test instrument. Herein, we present a flexible PTE photodetector capable of dual-mode output, combining electrical and optical signal generation for enhanced functionality. Using solution processing, high-quality MXene thin films are assembled on asymmetric electrodes as the photosensitive layer. The geometrically asymmetric electrode design significantly enhances the responsivity, achieving 0.33 mA W−1 under infrared illumination, twice that of the symmetrical configuration. This improvement stems from optimized photothermal conversion and an expanded temperature gradient. The PTE device maintains stable performance after 300 bending cycles, demonstrating excellent flexibility. A new energy conversion pathway has been established by coupling the photothermal conversion of MXene with thermochromic composite materials, leading to a real-time visualization of invisible infrared radiation. Leveraging this functionality, we demonstrate the first human–machine collaborative infrared imaging system, wherein the dual-mode photodetector arrays synchronously generate human-readable pattern and machine-readable pattern. Our study not only provides a new solution for functional integration of flexible photodetectors, but also sets a new benchmark for human–machine collaborative optoelectronics. Highlights: 1 An optical/electric dual-mode photodetector array for human–machine collaborative infrared imaging was demonstrated. 2 The responsivity of the photothermoelectric photodetector was improved by the geometrically asymmetric electrodes. 3 Coupling the photothermal conversion of MXene with thermochromic composites enabled a direct visualization of invisible infrared radiation.